Acidentes por quedas: assistência profissional na estratégia saúde da família - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Introduction: Falls can be understood as accidental events, resulting from changes in the person's position. Objective: To know the assistance of professionals of the Family Health Strategy in accidents due to falls. Methodology: Exploratory, descriptive-analytical, cross-sectional study. Conducted through semi-structured interviews recorded with 72 professionals from Family Health Strategies in a municipality on the western border of Rio Grande do Sul. Qualitative analysis was applied using the IRAMUTEC software. Results: Descending Hierarchical Classification presented six classes ratified by the similarity analysis and the word cloud method. Conclusion: There is professional assistance by the Family Health Strategy in accidents involving falls. Especially for contact with the Mobile Emergency Service.
Fall accidents: professional assistance in the family health strategy
Keywords: Acidente por quedas; Saúde da família; Profissionais da saúde; Accident due to falls; Family Health; Health professionals; Enfermagem; Nursing; CNPQ::CIENCIAS DA SAUDE